2018
DOI: 10.3389/fpls.2018.01390
|View full text |Cite
|
Sign up to set email alerts
|

Both NaCl and H2O2 Long-Term Stresses Affect Basal Cytosolic Ca2+ Levels but Only NaCl Alters Cytosolic Ca2+ Signatures in Arabidopsis

Abstract: Salinity is one of the formidable environmental factors that affect plant growth and development and constrain agricultural productivity. Experimentally imposed short-term NaCl treatment triggers a transient increase in cytosolic free Ca2+ concentration ([Ca2+]i) via Ca2+ influx across the plasma membrane. Salinity stress, as well as other stresses, induces the production of reactive oxygen species (ROS), such as H2O2. It is well established that short-term H2O2 treatment also triggers a transient increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…Previously, we have shown that [Ca 2+ ] i increases induced by salt stress and H 2 O 2 are similar, although aequorin imaging of lower temporal resolution was used (Jiang et al ., 2013; Liu et al ., 2018), in contrast to the drastic difference between those induced by abiotic vs biotic stress (Cao et al ., 2017). Superficially similar responses of whole seedling [Ca 2+ ] i to 200 mM sorbitol and 100 mM NaCl have been observed previously, although the concentrations used were relatively low compared to those commonly used (Tracy et al ., 2008).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Previously, we have shown that [Ca 2+ ] i increases induced by salt stress and H 2 O 2 are similar, although aequorin imaging of lower temporal resolution was used (Jiang et al ., 2013; Liu et al ., 2018), in contrast to the drastic difference between those induced by abiotic vs biotic stress (Cao et al ., 2017). Superficially similar responses of whole seedling [Ca 2+ ] i to 200 mM sorbitol and 100 mM NaCl have been observed previously, although the concentrations used were relatively low compared to those commonly used (Tracy et al ., 2008).…”
Section: Resultsmentioning
confidence: 96%
“…There are a few key steps to determine the selectivity between Stimulus A and Stimulus B (S‐B) in the s‐a mutant using the method developed here as well our previous studies (Jiang et al ., 2013; Cao et al ., 2017; Liu et al ., 2018). Similar Ca 2+ signaling levels induced by S‐A and S‐B, which are obtained from their dose curves, should be used for comparison in the wild‐type, such as NaCl and H 2 O 2 (Jiang et al ., 2013) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the earliest events found in salinity stressed plant cells is an elevation in cytosolic free Ca 2+ (Liu et al, 2018;Tracy, Gilliham, Dodd, Webb, & Tester, 2008;Wang, Teng, Zhu, Zhang, & Liu, 2019). NADPH oxidase possesses two Ca 2+ -binding sites at the N-terminal of its EF-hand (Marino, Dunand, Puppo, & Pauly, 2012).…”
Section: Ros Production and Signalling In Plant Adaptation To Salinitymentioning
confidence: 99%
“…One of these regulators is calmodulins-like 10, which interacts with AsA biosynthesis enzyme phosphomannomutase (PMM) to modulate enzyme activities and AsA pool ( Cho et al, 2016 ), which suggested the role of calcium (Ca 2+ ) in AsA biosynthesis. It has been known that Ca 2+ signaling is triggered by ROS accumulation ( Rentel and Knight, 2004 ) and Ca 2+ wave is induced under salt stress ( Choi et al, 2014 ; Liu et al, 2018 ). A chloroplast protein, QUASIMODO1 (QUA1), functions upstream of a thylakoid-localized Ca 2+ sensor, CAS, to mediate Ca 2+ signaling under salt stress ( Zheng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%